NILAI TAMBAH DAN SALURAN PEMASARAN IKAN ROA ASAP DI DESA LENGGETAN KECAMATAN BANGKURUNG - Labasi, Yosua; Rustiawati, Yuni; Puspapratiwi, Dian (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2025)
The processing of fishery products through smoking activities is an important effort in increasing the added value of products and the income of coastal communities. This study aims to analyze the smoking process of roa fish, the added value generated from the processing activities, and the marketing channels of smoked roa fish in Lenggetan Village, Bangkurung District, Banggai Laut Regency. The study was conducted from July to October 2024 using a census method on all 18 smoked roa fish processors, and involving two collectors as supporting informants. The data used consisted of primary and secondary data. The added value analysis was conducted using the Hayami value-added calculation approach, while the marketing channels were analyzed descriptively. The results of the study indicate that the smoking process of roa fish includes the stages of washing, transportation, clamping and tying, arranging, smoking, and packaging. In one production process, an average of 25 packs of smoked roa fish are produced with a selling price of IDR 200,000 per pack. The added value obtained from processing roa fish into smoked roa fish is IDR 2,150,754 per production, which indicates that the roa fish smoking business is classified as having high added value. The marketing channels used consist of two patterns, namely direct sales from processors to consumers and sales through collecting traders who then distribute the product outside the region. The results of this study indicate that the roa fish smoking business in Lenggetan Village is feasible to be developed because it is able to provide added value and economic benefits for business actors.